Extensor lag in patients after total knee arthroplasty with and without pre-operative rehabilitation regime: a short report - Ilyas, Umer; Wajida Perveen; Akhtar, Muhammad; Hashmi, Riaz; Amin, Ijaz; Mehmood Bhatti, Zahid (Journal of the Pakistan Medical Association, 2022)
Total knee arthroplasty is gaining popularity in individuals with advanced stages of knee osteoarthritis among the affording economic class. The aim of the study was to assess the effects of preoperative rehabilitation in the management of post-operative quadriceps lag. The study design was non-randomised clinical study conducted from January 2017 to March 2017 at Ghurki Trust Teaching Hospital, Lahore, Pakistan. Non probability convenient sampling technique was applied to collect data of 30 patients with TKA. The data was collected by self-designed questionnaire, and goniometric range of knee extension was used as the main outcome. Independent sample t-test was applied to assess the difference between the groups. The mean age of the patients was 64.37±11.66 years. The mean score for Extensor Lag with pre-operative rehabilitation regime was 12.53º±36.57º and without this regime it was 23.20 ±79.18º (p value 0.005 & t-value -3.035). —Continue